PERSEPSI IBU TERHADAP GEJALA DEPRESI PADA PERIODE KEHAMILAN DI PMB MARLINA - Dona Tri Sundari; Fyzria Qudratullah; Ria Gustiani (Jurnal Kesehatan dan Pembangunan, 2026)
Depression is a mood disorder characterized by feelings of sadness, anxiety, guilt, worthlessness, restlessness, sleep disturbances, and thoughts of suicide or harming the baby. Depression is a mental health disorder that has negative impacts and can affect a person’s way of thinking. Data from the World Health Organization (WHO) indicate that the global prevalence of depressive mental disorders is 4.6% among women, which is higher than that among men at 2.6%. Recent data show that approximately 10% of pregnant women worldwide experience depression. In Indonesia, the prevalence of antenatal depression is reported to be 20% among women in the second and third trimesters of pregnancy. Depressive symptoms increase by 16% in the third trimester and may persist up to four weeks and three months postpartum. Central Java Province has a prevalence of emotional mental disorders of 7.7% among 95,460 residents. The aim of this study was to determine mothers’ perceptions of depressive symptoms during pregnancy. This study employed a qualitative research method using a phenomenological approach. Data were collected through in-depth interviews with mothers selected as research subjects. The interviews aimed to obtain in-depth information regarding mothers’ experiences and perceptions of depressive symptoms during pregnancy. The findings of this study were guided by phenomenological research in midwifery, using video recording tools and in-depth interview guidelines, focusing on cases related to mothers’ perceptions of depressive symptoms during the pregnancy period.